Impacts of Morphological Characteristics on Target Strength of Chub Mackerel (Scomber japonicus) in the Northwest Pacific Ocean - Tong, Jianfeng; Xue, Minghua; Zhu, Zhenhong; Wang, Weiqi; Tian, Siquan (Frontiers in Marine Science, 2022)
Chub mackerel (Scomber japonicus) is an important commercial fish in the Northwest Pacific Ocean. Accurate target strength (TS) underpins acoustic stock assessment, but the TS of S. japonicus is still poorly understood. In this study, the Kirchhoff-ray mode model was used to estimate the TS of S. japonicus and its relationship with sound wave frequency and fish morphology. The results revealed that TS values varied with pitch angle shifts, with the impact on fish scattering strength being greater at higher frequency. This is less important because 38 kHz has been used for the biomass assessment of these fish resources. At frequencies of 38 kHz, 70 kHz, 120 kHz and 200 kHz, TS was greatest at a pitch angle range of -10° to 0°, which was related to the angle of the swim bladder tilt. There were almost no differences between TS estimated using the measured pitch angle distributions and using the universal distribution. When the measured pitch angle was N[-3°,4°], the average TS of S. japonicus with body length of 12.04–22.17 cm at four frequencies was -48.88 dB, -49.14 dB, -49.75 dB and -48.55 dB, respectively. The regression intercept (b_20) in TS–body length equation was -73.27 dB, -73.56 dB, -74.18 dB and -73.46 dB, respectively. Variation in TS range at 0–300 m depth was about 10 dB. The simulated broadband target strength spectrum shows the scattering characteristics of individuals with different swim bladder length between 0–250 kHz. These results could be used for identification of S. japonicus in echograms and provide reference for acoustic stock assessment of S. japonicus in the Northwest Pacific Ocean.